THE ALM (AUDIO-LINGUAL METHOD) FOR ENHANCING SPEAKING SKILL OF EFL STUDENTS IN INFORMATION TECHNOLOGY DEPARTMENT: METODE ALM (AUDIO-LINGUAL) UNTUK MENINGKATKAN KETERAMPILAN BERBICARA MAHASISWA EFL DI JURUSAN TEKNOLOGI INFORMASI - Ramadhani, Putri (Indonesian Journal of ELT and Applied Linguistics, 2024)
THE ALM (AUDIO-LINGUAL METHOD) FOR ENHANCING SPEAKING SKILL OF EFL STUDENTS IN INFORMATION TECHNOLOGY DEPARTMENT Putri Ramadhani pramadhaniput@gmail.com Fakultas Ilmu Komputer dan Teknologi Informasi, Universitas Budi Darma Medan Abstract Investigating the efficacy of the audio-lingual approach taught in the classroom by an English lecturer to second-semester information technology students who are learning English as a foreign language (EFL) is the significance of this study. ESP (English for Specific Purpose) is taught to EFL students with an emphasis on computers and technology. The teaching approach known as the audio-lingual method (ALM) is founded on psychological behaviorism and structural linguistics. Enabling students to speak the target language like native speakers is the aim of this approach. This approach can help EFL students develop language habits through drilling and mimicry. It can be difficult to teach speaking to EFL students in Indonesia because of the influence of mother tongues and traditional languages. Prior studies indicate this method is able to improve speaking skill ability. The result of this research shows speaking skill of EFL students gradually improve week by week by doing observation with pre-test and post-tet during four weeks Keywords: Audio-Lingual Method, EFL students, Speaking Skill